(untitled) (Northern International Medical College Journal, 2018)
Background : Premature Rupture of Membrane (PROM) is a significant obstetric emergency where a normal pregnancy suddenly becomes a high risk one. It can cause serious complications of mother and fetus. Patient’s history, per speculum vaginal with Nitrazine paper test and Fern test considered as gold standard for diagnosis of PROM. But these multiple tests are hazardous and time consuming. Therefore Alpha-Feto Protein (AFP) test is a single sensitive test for proper diagnosis of PROM. Objective : To evaluate the accuracy of Alpha-Feto protein in vaginal fluid as a diagnostic tool of PROM. Method : It was a cross sectional study, carried out among 120 pregnant women who had the gestational age between 28th to 40th week of pregnancy. Sample was collected purposively and divided into two groups. In group-I-62 suspected PROM patients were selected who gave the history of per vaginal watery discharge and was found positive in per speculum examination (P/S). In group-II-58 non PROM pregnant patients were selected. Then in group-I, Nitrazine paper test and Fern test were done to confirme PROM patients. Both groups AFP test was done by AxSYM auto analyzer. Finally the accuracy of AFP was evaluated against the gold standard test. Result : It was found that AFP concentration was significantly higher in group-I of suspected PROM patients (30- 502ng/ml) than in group-II (0-40ng/ml). Among 62 suspected PROM patients 49 were found gold standard (Nitrogen paper test and Fern test) positive. Out of these 49 confirmed PROM patients 48 was found positive in Alpha-Feto protein test. The sensitivity of AFP test was found 98%, specificity was 84.6% and accuracy was 95.1%. Conclusion : As Alpha-Feto protein in vaginal fluid was found highly accurate (95.1%) for diagnosis of PROM. Therefore, AFP test can be used as a single sensitive test for diagnosis of PROM. Northern International Medical College Journal Vol.10(1) Jul 2018: 335-338